The Deaf-blind and their rehabilitation services in India - Rama Mohan Babu P; Rathna N (Journal of All India Institute of Speech and Hearing, 1972)
A deaf-blind child is one whose sense of hearing is non-functional for theordinary purposes of life with or without a hearing aid and whose vision is nonfunctionalfor the ordinary purposes of life with or without correcting glasses